2021
DOI: 10.1542/hpeds.2020-003038
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Parents of Hospitalized Children Living With Medical Complexity

Abstract: BACKGROUND AND OBJECTIVES Children living with medical complexity (CMC) experience frequent hospital admissions. Validated patient-reported experience measures may inform care improvements in this cohort. Our objectives were to examine the comprehensive inpatient experience of CMC by using a validated patient-reported experience measure and compare the results with all other respondents at 2 academic pediatric hospitals in a western Canadian province. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In another report, we showed that women who were hospitalized due to ischaemic heart disease reported a worse experience on over half of the 37 survey questions examined, when compared with their male counterparts [ 39 ]. Similarly, we showed that parents of hospitalized children living with medical complexity reported a poorer experience on over 70% of the survey questions, when compared with parents of other hospitalized children [ 40 ]. Recently, we showed that adults who were hospitalized during the early months of the COVID-19 pandemic reported experiences that were in many aspects, better that those who were hospitalized during the previous year (pre-pandemic) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another report, we showed that women who were hospitalized due to ischaemic heart disease reported a worse experience on over half of the 37 survey questions examined, when compared with their male counterparts [ 39 ]. Similarly, we showed that parents of hospitalized children living with medical complexity reported a poorer experience on over 70% of the survey questions, when compared with parents of other hospitalized children [ 40 ]. Recently, we showed that adults who were hospitalized during the early months of the COVID-19 pandemic reported experiences that were in many aspects, better that those who were hospitalized during the previous year (pre-pandemic) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Experience of parents of hospitalized children living with medical complexity (CMC) [40] Examine the comprehensive inpatient experience of CMC, and compare the results with all other respondents at two academic pediatric hospitals.…”
Section: Cpes-ic Dadmentioning
confidence: 99%